Examining individual, job and perceived organizational climate factors in relation to the knowledge sharing behavior - Balozi, Mohamed Abbasi (2017)
This study examined the direct relationship between individual capabilities, career advancement, personal values, job characteristics, perceived organizational climate and knowledge- sharing behavior. The study also investigated the moderating effect of subjective norms on the relationship between individual capabilities, career advancement, personal values, job characteristics, perceived organizational climate and knowledge- sharing behavior. A total of 650 questionnaires were personally distributed to respondents from five Tanzanian public hospitals (Muhimbili National Hospital, Ligula Referral Hospital, Mnazi Mmoja Hospital, Sekou Toure Reginal Hospital Mwanza and Mbeya Referral Hospital) after permission was granted by the hospital management. Out of the 650 questionnaires distributed, 476 questionnaires were returned, representing a response rate of 73%. However, only 439 questionnaires were usable for final analysis. The hypotheses for direct and moderating effects were tested using Smart PLS. The findings of the PLS path model indicated that individual capabilities, career advancement, personal values, and perceived organizational climate are significantly and positively related to knowledge- sharing behavior. Regarding the subjective norms as a moderator in the relationship between exogenous latent variables and the endogenous latent variable, subjective norms were found to moderate the relationship between individual capabilities, job characteristics, perceived organizational climate and knowledge- sharing behavior. The research results reported in this study suggest the need to enhance individual capabilities, career advancement, personal values, and perceived organizational climate as a way of encouraging knowledge- sharing behavior among the healthcare professionals. Apart from that, the hospital management also needs to consider the role of subjective norms when planning to enhance healthcare professionals’ knowledge- sharing behavior, especially when involving individual capabilities, job characteristics and perceived organizational climate.